2016
DOI: 10.1038/mto.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming antitumor immunity against chemoresistant ovarian cancer by a CXCR4 antagonist-armed viral oncotherapy

Abstract: Ovarian cancer remains the most lethal gynecologic malignancy owing to late detection, intrinsic and acquired chemoresistance, and remarkable heterogeneity. Here, we explored approaches to inhibit metastatic growth of murine and human ovarian tumor variants resistant to paclitaxel and carboplatin by oncolytic vaccinia virus expressing a CXCR4 antagonist to target the CXCL12 chemokine/CXCR4 receptor signaling axis alone or in combination with doxorubicin. The resistant variants exhibited augmented expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 64 publications
1
25
0
Order By: Relevance
“…CXCR4 antagonist plerixafor combined with anti-PD-1 therapy showed the most pronounced tumor growth delay, and was associated with increased intratumoral penetration and activation of CD8 + T lymphocytes (241). A novel strategy for the treatment of drug-resistant ovarian cancer combines chemotherapy to increase immunogenic cell death and virally delivered CXCR4 to reverse the immunosuppressive tumor microenvironment (242). Ovarian cancer of murine and human ovarian tumor variants resistant to paclitaxel and carboplatin were infected with oncolytic vaccinia virus expressing a CXCR4 antagonist and were +/– treated in combination with doxorubicin.…”
Section: Physiologic Role Of Cxcr4 In the Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCR4 antagonist plerixafor combined with anti-PD-1 therapy showed the most pronounced tumor growth delay, and was associated with increased intratumoral penetration and activation of CD8 + T lymphocytes (241). A novel strategy for the treatment of drug-resistant ovarian cancer combines chemotherapy to increase immunogenic cell death and virally delivered CXCR4 to reverse the immunosuppressive tumor microenvironment (242). Ovarian cancer of murine and human ovarian tumor variants resistant to paclitaxel and carboplatin were infected with oncolytic vaccinia virus expressing a CXCR4 antagonist and were +/– treated in combination with doxorubicin.…”
Section: Physiologic Role Of Cxcr4 In the Immune Systemmentioning
confidence: 99%
“…Antitumor immune responses in this model culminated in the control of metastatic tumor growth and tumor-free survival. Mechanistically, the authors showed combination treatment increased apoptosis and phagocytosis of tumor material by DCs which efficiently induced adaptive antitumor immunity, reflected by increased intratumoral infiltration of antitumor CD8 + T cells and reduced immunosuppressive Tregs (242). Based on these results (Figure 2), the MORPHEUS clinical trials were started including treatment arms combining immune-checkpoint inhibitors with CXCR4 inhibition (NCT03193190, NCT03281369 and NCT03337698 for pancreatic cancer, gastric cancer and non-small cell lung cancer, respectively).…”
Section: Physiologic Role Of Cxcr4 In the Immune Systemmentioning
confidence: 99%
“…The potential of combining VACV with ICD inducers has been explored for drug-resistant ovarian cancers. Komorowski et al (110) combined recombinant VACV with doxorubicin, a standard of care anthracycline. In vitro treatment of ovarian cancer cells with VACV enhanced susceptibility to doxorubicin, likely mediated through type I IFNs, and increased DC tumor Ag uptake.…”
Section: Ovs: Anticancer Vaccines and Icd Inducersmentioning
confidence: 99%
“…For example, the systemic delivery of a vaccinia OV armed with a CXCR4 antagonist to mice with orthotopic mammary tumours disrupted the interaction between tumour cell CXCR4 and CXCL-12 present in the stromal microenvironment. This lead to tumour growth retardation, a reduction of spontaneous metastasis, the destruction of tumour associated vasculature and increased overall tumour-free survival [ 129 ].…”
Section: Potential Approaches To Combine Oncolytic Virotherapy With Cmentioning
confidence: 99%